2019
DOI: 10.3390/su11195212
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the Perception Gap between Management and Customers on DINESERV Attributes: The Korean All-You-Can-Eat Buffet

Abstract: Our study is based on the premise that there are differences between the key service attributes that restaurant managers prioritize and crucial DINESERV attributes that are important to customers’ perception of their experience at a restaurant. This paper investigated the perception gap between operators and customers on the service attributes of Korean all-you-can-eat buffet restaurants, and it suggests strategic alternatives to bridge this perception gap. To investigate this perception gap, we first used the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Like Kim and Choi [31], we investigated which factors-such as food quality, service quality, atmosphere and interior, and price and value-affect customer satisfaction, which, in turn, determines revisit intentions and likelihood of recommendation, using a factor analysis and a regression analysis.…”
Section: Research Model and Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…Like Kim and Choi [31], we investigated which factors-such as food quality, service quality, atmosphere and interior, and price and value-affect customer satisfaction, which, in turn, determines revisit intentions and likelihood of recommendation, using a factor analysis and a regression analysis.…”
Section: Research Model and Methodologymentioning
confidence: 99%
“…Kim et al [42] found that the five restaurant factors-food quality, service quality, price and value, atmosphere, and convenience-had a significant impact on the customer's satisfaction with dining facilities [43]. Kim and Choi [31] used four factors-food quality, service quality, interior, and price and value-to investigate the perception gap of service attributes between operators and customers. Like Kim and Choi [31], we investigated how four factors-food quality, service quality, atmosphere and interior, and price and value-affect customer satisfaction, which, in turn, determines revisit intentions and likelihood of recommendation, using a factor analysis and a regression analysis.…”
Section: Research Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to measure the service quality in restaurant, Stevens, Knutson and Patton [14] then modify the SERVQUAL by developing the DINESERV instrument. This measurement tool then used by many authors to assess the restaurants' service quality, recently it was used in Indonesia [15], Korea [16], and even Italy [10].…”
Section: Literature Review 21 Service Qualitymentioning
confidence: 99%
“…Those provided strategies were based on big and fully established firms which have capabilities to apply such strategies. Service operator's perspective [16] and firms' capabilities [18] shall be taken into account in determining service quality improvement strategy. Several strategies that can be used by MSMEs are including strategic use of complaints, standardizing tasks and service delivery, technical and interpersonal training [18], and introducing a customer oriented service to its employees [19].…”
Section: Literature Review 21 Service Qualitymentioning
confidence: 99%